The German statutory pension scheme: Balance sheet, cross-sectional internal rates of return and implicit tax rates - Christoph Metzger (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2016)
We present a framework for accounting of the German statutory pension scheme and estimate a balance sheet for the years 2005 until 2012. Extending and applying the methodology proposed by Settergren and Mikula (2005), we estimate the cross-sectional internal rates of return of the German pension scheme over this period. We are able to show that the cross-sectional internal rate of return is mainly financed by increasing contributions and by changing the liabilities not backed by assets. Additionally, our results reveal that from an expenditure perspective, the major part of the internal rate of return is resulting from changing longevity rather than indexation of pension entitlements. Finally, we prove that from a cross-sectional perspective the implicit tax of a pension scheme can mainly be interpreted as an “implicit wealth tax” on pension wealth and subsequently present empirical estimates for these cross-sectional implicit tax rates.
Keywords: E01; H55; H83; H87; 330; accounting of pension schemes; balance sheet; internal rate of return; implicit tax; fiscal sustainability